Gender Representation in Brazilian Computer Science Conferences - Dal Pizzol, Natália; Barbosa, Eduardo Dos Santos; Musse, Soraia Raupp (Anais do Women in Information Technology (WIT); 2022: Anais do XVI Women in Information TechnologyDO - 10.5753/wit.2022.222939, 2022)
This study presents an automated bibliometric analysis of 6569 research papers published in thirteen Brazilian Computer Science Society (SBC) conferences from 1999 to 2021. Our primary goal was to gather data to understand the gender representation in publications in the field of Computer Science. We applied a systematic assignment of gender to 23.573 listed papers authorships, finding that the gender gap for women is significant, with female authors being under-represented in all years of the study.